2007
DOI: 10.1089/apc.2007.0027
|View full text |Cite
|
Sign up to set email alerts
|

Condom Acquisition and Preferences within a Sample of Sexually Active Gay and Bisexual Men in the Southern United States

Abstract: Health departments, community-based organizations (CBOs), and AIDS service organizations (ASOs) in the United States and abroad distribute large quantities of free condoms to sexually active individuals; however, little is known about where individuals who use condoms actually acquire them. This community-based participatory research (CBPR) study was designed to identify factors associated with the use of free condoms during most recent anal intercourse among self-identifying gay and bisexual men who reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…One 2007 study of brand and color preference was conducted only in African American MSM, who preferred Trojan brand and non-colored condoms. 11 In a 1993 study of men of all sexual orientations, Grady et al gave respondents a list of condom characteristics and asked them to choose all characteristics that they look for when selecting a condom. Only three characteristics included could be considered separate condom types-thin, color, and ribbed-the rest were general condom characteristics (e.g., easy to put on, stays on, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…One 2007 study of brand and color preference was conducted only in African American MSM, who preferred Trojan brand and non-colored condoms. 11 In a 1993 study of men of all sexual orientations, Grady et al gave respondents a list of condom characteristics and asked them to choose all characteristics that they look for when selecting a condom. Only three characteristics included could be considered separate condom types-thin, color, and ribbed-the rest were general condom characteristics (e.g., easy to put on, stays on, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…This sample varied significantly from the recent study by Rhodes and colleagues, 10 in that ours primarily comprised heterosexually identified men, given that we collected data nationally rather than at GLBT events. However, consistent with that study's findings, men who identified as gay or bisexual were more likely to report that condoms they had used recently had been acquired only from free sources, although heterosexual men also reported frequently accessing free condoms.…”
Section: Discussionmentioning
confidence: 99%
“…9 Expansive condomdistribution campaigns have been implemented by those typically leading HIV-and STI-prevention efforts in such communities, such as local health departments, STI and HIV treatment clinics, and other community-based agencies focused on sexual health. 10 A recent study found that 69% of individuals who had received a condom during a city-led distribution program in New York reported having used the condom, providing evidence that condom-distribution and -marketing campaigns are effective mechanisms for driving actual condom use. 11 Condoms may be acquired, often at no cost, through these campaigns implemented by public health organizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A distinctive feature of CBPR is that research should move towards action through translation of findings into their application in the community (Arcury, Austin, Quandt, & Saavedra, 1999; Cornwall & Jewkes, 1995; Israel, Eng, Schulz, & Parker, 2005; Minkler, 2005; Rhodes, Eng, et al, 2007; Rhodes, et al, 2006; Rhodes, Hergenrather, Yee, et al, 2007; Solomon, Card, & Malow, 2006; Viswanathan, et al, 2004). Such action may include further research to understand phenomena to intervene more effectively; or intervention development, implementation, and/or evaluation.…”
Section: Community-based Participatory Research Definedmentioning
confidence: 99%